Study of Spectral and Thermodynamics properties for Hydrogen Sulfide (H2S) - Abdul-Hakim Shakor M (Kirkuk Journal of Science, 2012)
In this research theoretical semi – empirical calculations using PM3 method to study the molecular structure for H2S in Infra-red regin by using MOPAC, it is semi-empirical molecular orbital program ,Mopac using semi-empirical quantum mechanic for Hamiltonen through PM3 method, then study and calculated some of spectroscopy and thermodynamics properties for this molecule and determine the minimum total energy at equilibrium structure for molecule, this study and calculation yielded the equilibrium geometry distance, energetic value, for H2S total energy was (-217.03eV) at equilibrium distance(1.3Å) Through unharmonic potential of energy curve we founded the spectroscopic dissociation energy for this molecule is(8.81eV). The main purpose from this research calculate study the fundamental vibrational frequencies, absorption spectrum of molecule was between (1192.72 ,1808.53, 1812.91) cm-1 and intensity a absorption band was (7.58, 12.63 , 15.197) respectively. And using Hyper-chem program including occupied molecular orbital and unoccupied molecular orbital with highest energy value ( HOMA) and lawest energy value (LUMO), Were for H2S (EHOMO = -9.63eV) (ELUMO= 0.552eV) and calculate energy gab between EHOMO, ELUMO was ( Eg = 10.128eV) . From final matrix we get on the Thermodynamics properties at many degree of heating such as heat of formation (∆Hf) for H2S was (- 0.897 kcal/mal ) enthalpy ( 2397.6599 cal/mol), heat capacity ( 8.214 cal/ mal.K), entropy( 54.904 cal/mal .K ). And Gibbs free energy ( -14.0737 kcal/ mol).These properties taken at standard heating degree (298K) and agreement with experimental result.